PENERAPAN MOBILE LEARNING DALAM PENDIDIKAN JASMANI DAN OLAHRAGA - Syafruddin, Muhammad Akbar (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The progress of science and technology is very rapid. Advances in science and technology in the field of education encourage more practical and interesting learning experiences, which aim to improve the overall quality of education. Smartphone technology presents promising prospects in creating educational resources in schools, given the widespread ownership of smartphones among students. This research aims to explain the application of mobile learning in educational environments, with a special focus on its use in the field of Physical Education, Sports and Health (PJOK). This article uses a literature study method which utilizes various research results and other sources of information to solve the problems raised in this research. The library sources in this article come from Google Scholar, Researchgate, and Elsevier. It is hoped that this literature review on mobile learning will provide a basic resource for future research.